A reassessment of the multiaxial ductility C* creep crack growth equation based on the strain energy integral of the HRR singular field terms. (August 2019) - Payten, Warwick
Highlights: Strain energy density of the HRR field is used to calculate the multiaxial ductility. Multiaxial ductility factor is influenced by the entire damage zone. Model is based on the equivalency of plastic and elastic strain energy. Resulting factor is significantly smaller than currently used and in assessment codes. Conservatism in assessment codes could lowered from 30 to 3 times plane stress. Abstract: A revaluation of the upper bound plane strain multiaxial C* crack growth rates is undertaken for a range of materials. The analysis assumes that the multiaxial ductility factor can be approximated by taking the integrated dimensionless deviatoric and hydrostatic strain energy density of the HRR singular fields. Using the equivalency approximation between the plastic and elastic strain energy, a damage mechanics approach is used to determine the crack tip triaxial constraint. The new multiaxial factor was found to be independent of the power law behaviour, and for plane stress HRR fields gave a multiaxial factor of close to one. The new factor enables estimates of the upper bound crack rates under plane strain in the Nikbin Smith Webster equation to be undertaken. Creep crack growth data from nine materials were used to assess the new approximation for upper bound crack growth rates. The results suggest the current upper bound plane strain crack growth rates could be decreased from the current thirty times to three times the plane stress results for a range of materials.